“DEVONU LUG„OTIT-TURK” VA O„ZBEK SHEVALARI: O„XSHASHLIK VA FARQLAR - Muhsinjonova Shirinoy Asliddin qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This thesis contains ideas about the alternatives of lexical units in Mahmud Kashgari's work “Devonu lug„otit-turk” in the modern Uzbek dialect. In the Qarluq, Kipchak and Oghuz dialects, some units characteristic of the lexicon of the work have been preserved to a certain extent, and in some of them changes are observed in the process of historical development, while in others there are almost no gradual changes.